Principal Leadership Practices for Strengthening Teacher Competence in Primary Education - Hikmah Hikmah; Reva Maria Valianti; Yessi Fitriani (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examined principal leadership practices for strengthening teacher competence, the conditions that supported or constrained those practices, and the strategies used to address the constraints. A descriptive qualitative case study was conducted at a public primary school in South Sumatra, Indonesia. Participants were one principal and three classroom teachers selected purposively because of their direct involvement in teacher development activities. Data were generated through semi-structured interviews, non-participant observation, and document analysis, then analyzed through data condensation, data display, thematic comparison, and conclusion verification. Trustworthiness was enhanced through source and technique triangulation. The findings show that teacher development was sustained through an integrated set of seven leadership roles: educator, manager, administrator, supervisor, leader, innovator, and motivator. These roles were enacted through Teacher Working Group participation, internal coaching, scheduled academic supervision, assistance with instructional administration, encouragement of digital learning, collegial problem solving, and recognition of teacher effort. Enabling conditions included the principal’s commitment, collegial cooperation, teacher motivation, professional learning opportunities, and basic infrastructure. Constraints involved limited funding and time, unequal digital competence, and administrative workload. The study contributes a context-sensitive model showing that principal leadership strengthens teacher competence when professional learning, supervision, organizational support, and adaptive problem solving operate as a coherent cycle rather than as separate activities.